The Development of Online Food Reservation for Restaurant Kahfi using Structured Approach - Yahya, Muhammad Najmi; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2022)
Nowadays, information technology plays a big role, where it used to store, manipulate, distribute or create information. This is no exception in the field of food and beverage, which uses information technology application optimally to promote and manage food sales services. Hence, to follow the era of technology, an Online Food Reservation for Restaurant Kahfi is developed where it is a web-based system where customers are able to view and order various courses available in the restaurant. The system is developed to give advantages to the customer where the customer can order the food from the website and come to the restaurant with a reservation code. By this mean, it will lessen the waiting time as the chef has known in advance the order list made by the customers. Hence, to achieve these goals, the proposed web-based system applies information system method where that method is a web-technologies for delivering information and services to users. This system uses Waterfall Model Development to develop this system where this model is easy to understand and less complex. Meanwhile, Xampp and PhpMyAdmin are used to build the system. As the output of this project, it is hoped that customer who wait less for order can be served and also the management can improve their efficiency in restaurant management.